AM251 induces apoptosis and G2/M cell cycle arrest in A375 human melanoma cells. Issue 7 (August 2015) - Carpi, Sara; Fogli, Stefano; Romanini, Antonella; Pellegrino, Mario; Adinolfi, Barbara; Podestà, Adriano; Costa, Barbara; Da Pozzo, Eleonora; Martini, Claudia; Breschi, Maria Cristina; Nieri, Paola
Abstract : Human cutaneous melanoma is an aggressive and chemotherapy-resistant type of cancer. AM251 is a cannabinoid type 1 (CB1) receptor antagonist/inverse agonist with off-target antitumor activity against pancreatic and colon cancer cells. The current study aimed to characterize the in-vitro antimelanoma activity of AM251. The BRAF V600E mutant melanoma cell line, A375, was used as an in-vitro model system. Characterization tools included a cell viability assay, nuclear morphology assessment, gene expression, western blot, flow cytometry with Annexin V–FITC/7-AAD double staining, cell cycle analyses, and measurements of changes in intracellular cAMP and calcium concentrations. AM251 exerted a marked cytotoxic effect against A375 human melanoma cells with potency comparable with that observed for cisplatin without significant changes in the human dermal fibroblasts viability. AM251, at a concentration that approximates the IC50, downregulated genes encoding antiapoptotic proteins (BCL2 and survivin) and increased transcription levels of proapoptotic BAX, induced alteration of Annexin V reactivity, DNA fragmentation, chromatin condensation in the cell nuclei, and G2/M phase arrest.AM251 also induced a 40% increase in the basal cAMP levels, but it did not affect intracellular calcium concentrations. The involvement of GPR55, TRPA1, and COX-2 in the AM251 mechanism of action was excluded. The combination of AM251 with celecoxib produced a synergistic antitumor activity, although the mechanism underlying this effect remains to be elucidated. This study provides the first evidence of a proapoptotic effect and G2/M cell cycle arrest of AM251 on A375 cells. This compound may be a potential prototype for the development of promising diarylpyrazole derivatives to be evaluated in human cutaneous melanoma.